A new modified internal fixation method of transconjunctival lower blepharoplasty. Issue 4 (30th January 2022) - Ou, Kuangwen; Huang, Wenchi; Chin, Sokheng
Abstract: In transconjunctival lower eyelid blepharoplasty with pedicled fat transposition, internal fixation of the septal fat is always the most difficult step. We describe a new modified method that makes this procedure less time‐consuming and specific instruments unnecessary.